Composite electrolyte and preparation method and application thereof
By using MOF materials and amino-modified ligands with an average particle size of no more than 10 nm in the in-situ gel electrolyte, the problems of dispersion and rate performance of the electrolyte are solved, and the uniform dispersion and conductivity of the electrolyte are achieved. It significantly improves the magnification and low-temperature performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202411766492.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-01-03
AI Technical Summary
The application of existing in-situ gel electrolytes in large-scale batteries is limited by ionic conductivity. The average particle size of conventional inorganic ion conductors is large, making it difficult to maintain uniform dispersion, which affects the wetting and rate performance of the electrolyte.
Ultra-small size MOF materials with an average particle size of no more than 10 nm are used as the nucleation center of the composite electrolyte to promote dissociation and transmission of electrolyte salts, improve conductivity, and improve the dielectric constant and the performance of the conductive network through amino modification ligands.
It significantly improves the rate performance and low temperature performance of the in-situ gel system, ensures uniform dispersion and infiltration of the electrolyte in the battery cell, and enhances the conductivity of the electrolyte and the overall performance of the battery.
Smart Images

Figure SMS_8 
Figure SMS_9
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a composite electrolyte and a preparation method and application thereof. Background Art
[0002] The in-situ gel electrolyte system based on electrolyte and a small amount of polymer monomer is currently one of the most feasible routes to realize solid-state batteries. Although the ionic conductivity of this system is much higher than that of conventional polymer-based solid electrolytes, it still has a certain gap compared with electrolytes, which limits the application of in-situ gel systems in high-rate batteries. Therefore, it is necessary to further modify the in-situ gel system electrolyte.
[0003] At present, the modification of the in-situ gel system usually targets the structure of the polymer monomer, the polymerization method and the number of cross-links. However, since the polymer framework itself does not provide ion conductivity, its ion conductivity must be significantly lower than that of the liquid system. Therefore, it is necessary to add some additional materials that promote ion conduction. Inorganic ion conductors represented by oxides are a hot topic in current research. Although their lithium conductivity theory can improve the lithium ion conductivity of the in-situ gel electrolyte, it is found in practice that it is still difficult to meet the high rate requirements of the in-situ gel system. Therefore, it is urgent to develop an in-situ gel system composite electrolyte with improved rate performance. Summary of the invention
[0004] The present application aims to solve at least one of the technical problems existing in the prior art. To this end, the present application proposes a composite electrolyte of an in-situ gel system capable of improving rate performance, and a preparation method and application thereof.
[0005] In a first aspect of the present application, a composite electrolyte is provided. The raw materials for preparing the composite electrolyte include a polymer electrolyte. The polymer electrolyte is doped with a MOF material. The average particle size of the MOF material is not greater than 10 nm.
[0006] The composite electrolyte according to the first aspect of the present application has the following beneficial effects: During the experiment, the applicant noticed that the electrolyte of the in-situ gel system needs to stand in the battery cell for a period of time after injection, so the dispersibility of the inorganic filler in the electrolyte is very important. Conventional inorganic ion conductors have a large average particle size, which makes it difficult to maintain a uniform dispersion state in the electrolyte for a long time when used as inorganic fillers. The scheme of the present application selects ultra-small MOF with an average particle size of less than 10 nm. During in-situ curing, the MOF material can serve as a nucleation center to improve the gelation strength. After curing, it can promote the dissociation of electrolyte salts and help the transmission of electrolyte salts, effectively improving the electrolyte ion conductivity. And its average particle size is small enough that it will not be deposited on one side of the battery cell after injection, but can remain uniformly dispersed after standing for a long time. Ultimately, it is beneficial to the infiltration of the electrolyte and the uniform distribution of MOF in many aspects, improving the rate performance of the in-situ gel system.
[0007] In addition, ultra-small-sized MOF materials have lower porosity and more surface defects than conventional-sized MOF materials, and thus have higher dielectric constants. At the same time, ultra-small-sized MOF materials have more defect sites, larger surfaces, and more exposed Lewis acid sites than conventional-sized MOF materials. Both of these aspects are beneficial to the dissociation of lithium salts after gelation, thereby improving the conductivity of the gel electrolyte and, in turn, improving its multiple performance including rate performance.
[0008] In some embodiments of the present application, the mass percentage of MOF material in the polymer electrolyte is 0.01~60wt%, for example, it can be 0.01 wt%, 0.02 wt%, 0.03 wt%, 0.04 wt%, 0.05 wt%, 0.06 wt%, 0.08 wt%, 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.8 wt%, 1 wt%, 2 wt%, 3 wt%, 4wt%, 5 wt%, 6 wt%, 8 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%.
[0009] In some embodiments of the present application, the mass percentage of the MOF material in the polymer electrolyte is 0.01-50 wt %, 0.01-20 wt %.
[0010] In some embodiments of the present application, the MOF material includes at least one of UiO-based, MOF-based, IRMOF-based, ZIF-based, BTC-based, MIL-based, and HKUST-based MOF materials.
[0011] In some embodiments of the present application, the MOF material includes at least one of UiO-66, UiO-67, UiO-68, UiO-69, MOF-5, MOF-74, MOF-177, MOF-505, MOF-525, MOF-801, IRMOF-1, IRMOF-3, IRMOF-6, IRMOF-8, ZIF-7, ZIF-8, MIL-53, MIL-88, MIL-101, and HKUST-1.
[0012] In some embodiments of the present application, the average particle size of the MOF material can be detected by at least one of electron microscopy (such as transmission electron microscopy TEM or scanning electron microscopy SEM), dynamic light scattering (DLS), static light scattering (SLS), ultracentrifugal sedimentation, etc.
[0013] In some embodiments of the present application, the average particle size of the MOF material is 1 nm to 10 nm, for example, it can be 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, or 10 nm.
[0014] In some embodiments of the present application, the MOF material having an average particle size of no more than 10 nm is prepared by the following method: Preparation of metal oxygen clusters using metal salts; The metal oxygen clusters are mixed with ligands to react and synthesize MOF materials with an average particle size of no more than 10 nm.
[0015] By pre-synthesizing metal oxide clusters and using them as raw materials for synthesizing MOF materials, the effect of the acidity of metal salts on the dissociation of ligand carboxyl groups can be minimized.
[0016] In some embodiments, the method for the mixed reaction of metal oxygen clusters and ligands includes at least one of a solution method, a solvothermal method, a diffusion method, a sol-gel method, a stirring synthesis method, an ultrasonic microwave synthesis method, and the like.
[0017] In some embodiments, the solution method includes mixing the metal oxygen clusters with a second solvent and a ligand, reacting at room temperature, and then separating the MOF material.
[0018] In some embodiments, the mixed system of metal oxygen clusters further includes acetic acid.
[0019] In some embodiments, the mass ratio of metal oxygen clusters to ligands is 1:0.2-5, for example, it can be 1:0.3, 0.4, 0.5, 0.6, 0.8, 1, 1.2, 1.4, 1.6, 1.8, 2.
[0020] In some embodiments, the mass ratio of the metal oxygen clusters to the second solvent is 1:200-2000, for example, 1:200, 300, 400, 500, 600, 800, 1000, 1200, 1400, 1600, 1800, or 2000.
[0021] In some embodiments, the second solvent comprises an alcohol solvent. In some embodiments, the second solvent comprises at least one of methanol, ethanol, isopropanol, glycerol, ethylene glycol, n-butanol, and isoamyl alcohol.
[0022] In some embodiments, the separation method after the room temperature reaction is completed includes rotary evaporation until a small amount of liquid remains, collecting the liquid by centrifugation, washing, and drying to obtain the MOF material.
[0023] In some embodiments, the washing is performed using a third solvent.
[0024] In some embodiments, the third solvent includes at least one of ketones and alcohols.
[0025] In some embodiments, the third solvent includes at least one of methanol, ethanol, isopropanol, glycerol, ethylene glycol, n-butanol, isoamyl alcohol, and acetone.
[0026] In some embodiments, washing comprises centrifugation washing with acetone and ethanol, respectively.
[0027] In some embodiments, the temperature of the rotary evaporation is 20-30 °C.
[0028] In some embodiments, the method for preparing metal oxygen clusters from metal salts includes adding metal salts and acetic acid (or acetate) to a first solvent for dissolution, reacting at 100-300 °C for 0.5-24 hours, centrifuging, washing, and drying to obtain metal oxygen clusters. In some embodiments, the first solvent includes an alcohol solvent. In some embodiments, the first solvent includes at least one of methanol, ethanol, isopropanol, glycerol, ethylene glycol, n-butanol, and isopentanol.
[0029] In some embodiments, the MOF material includes a metal element and a ligand.
[0030] In some embodiments, the metal element includes at least one of Zn, Cu, Ni, Cd, Fe, Al, Zr, Cr, etc.
[0031] In some of these embodiments, the ligand contains a carboxyl group.
[0032] In some embodiments, the ligand is modified with an amino group. Specifically, the method includes but is not limited to pre-modifying the amino group on the ligand before preparation and then reacting with the metal oxygen cluster to generate the MOF material. The introduction of the amino group allows the MOF material to be doped in the gel electrolyte to further improve the ionic conductivity.
[0033] The above-mentioned synthesis method of MOF materials has a certain universality and can synthesize nanoparticles of different types of MOFs. In theory, all MOFs that use carboxyl ligands for coordination and can react at room temperature can be synthesized in this way, such as MOF-801.
[0034] In the synthesis process of MOF materials, metal oxygen clusters are used instead of metal salts as synthetic raw materials to avoid the difficulty of protonation caused by acidity. A large amount of ethanol is used as a solvent instead of water to increase the dissolution rate of organic ligands and accelerate the nucleation process of MOF. The synthesis process is carried out at room temperature to avoid the increase of surface energy caused by high temperature, which leads to the intensification of Ostwald ripening.
[0035] In some embodiments of the present application, the raw material for forming the polymer electrolyte includes a polymerized monomer.
[0036] In some embodiments of the present application, the raw materials for forming the polymer electrolyte further include a cross-linking agent.
[0037] In some embodiments of the present application, the raw materials for forming the polymer electrolyte further include an initiator.
[0038] In some embodiments of the present application, the total mass of the polymerized monomer, the cross-linking agent, and the initiator accounts for 0.1 to 99 wt% of the total mass of the raw materials for forming the polymer electrolyte, for example, 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.8 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 8 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, 70 wt%, 75 wt%, 80 wt%, 85 wt%, 90 wt%, 95 wt%, 96 wt%, 97 wt%, 98 wt%, and 99 wt%.
[0039] In some embodiments of the present application, the polymerizable monomer includes at least one of an acrylate monomer, an ether monomer, a carbonate monomer, an oxalate monomer, and an amide monomer.
[0040] The structural formula of acrylic acid ester monomer is as follows: ; Among them, R1 is H or a hydrocarbon group, and R2 is any one of a substituted or unsubstituted hydrocarbon group, an ether group, an ester group, a silane group, and a nitrile group.
[0041] In some embodiments, the molecular weight of R1 is no greater than 72.
[0042] In some embodiments, the molecular weight of R1 is no greater than 500.
[0043] In some embodiments, the substituent of the R2 group includes, but is not limited to, halogen, such as at least one of chlorine, bromine, and iodine. The number of substitutions may be single or multiple.
[0044] The structural formula of ether monomers is as follows: ; Wherein, R3 is a substituted or unsubstituted alkylene group, etherene group, esterene group, or silylene group.
[0045] In some embodiments, the molecular weight of R3 is no greater than 500.
[0046] In some embodiments, the substituent of the R3 group includes, but is not limited to, halogen, such as at least one of chlorine, bromine, and iodine. The number of substitutions may be single or multiple.
[0047] The structural formula of carbonate esters is any of the following: , .
[0048] In some embodiments, R4 and R5 are independently selected from H, any one of a substituted or unsubstituted hydrocarbon group, an ether group, an ester group, an alcohol group, a phenol group, a silane group, and a nitrile group.
[0049] In some embodiments, R6 is any one of a substituted or unsubstituted alkylene group, etherene group, esterene group, alcoholene group, phenolene group, silaneene group, and nitrileene group.
[0050] In some embodiments, the substituents of the R4, R5, and R6 groups include, but are not limited to, halogen, such as at least one of chlorine, bromine, and iodine. The number of substitutions may be single or multiple.
[0051] In some embodiments, the molecular weight of R4, R5, and R6 is no greater than 500.
[0052] The structural formula of carbonate esters is as follows: ; In some embodiments, R7 and R8 are independently selected from H, any one of a substituted or unsubstituted hydrocarbon group, an ether group, an ester group, an alcohol group, a phenol group, a silane group, and a nitrile group.
[0053] In some embodiments, the substituents of the R7 and R8 groups include, but are not limited to, halogen, such as at least one of chlorine, bromine, and iodine. The number of substitutions may be single or multiple.
[0054] In some embodiments, the molecular weight of R7 and R8 is no greater than 500.
[0055] The structural formula of the amide monomer is any of the following: , .
[0056] In some embodiments, R9, R 10 Each of the following is independently selected from any one of a substituted or unsubstituted alkylene group, an etherene group, an esterene group, an alcoholene group, a phenolene group, a silaneene group and a nitrileene group.
[0057] In some embodiments, R9, R 10 The substituents of the group include, but are not limited to, halogen, for example, at least one of chlorine, bromine, and iodine. The number of substitutions may be single or multiple.
[0058] In some embodiments, R9, R 10 The molecular weight is not more than 500.
[0059] In some embodiments, the ligand of the MOF material is modified with an amino group. The ultra-small size MOF material with amino-modified ligands can promote the improvement of the conductivity of the gel electrolyte with its higher dielectric constant. At the same time, the ultra-small particle MOF can penetrate into the interior of the electrode to a greater extent as part of the conductive network. The combination of the two makes the ultra-small size MOF material with amino-modified ligands have better low-temperature performance.
[0060] In some embodiments, the initiator includes at least one of an azo initiator and a peroxide initiator.
[0061] In some embodiments, the crosslinking agent includes at least one of acrylates, ethers, carbonates, oxalates, and amides having two or more crosslinking sites.
[0062] In some embodiments, the electrolyte salt includes any one of lithium salts, sodium salts, potassium salts, magnesium salts, calcium salts, and aluminum salts.
[0063] In some embodiments, the lithium salt includes at least one of LiPF6, LiBF4, LiDFOB, LiClO4, LiAsO6, LiBOB, LiFSI, LiTFSI, etc.
[0064] In a second aspect of the present application, a method for preparing a composite electrolyte is provided, the preparation method comprising the following steps: The raw materials of the polymer electrolyte and the MOF material are mixed, and solidified after standing to obtain a composite electrolyte.
[0065] In some embodiments, the raw materials of the polymer electrolyte include a solvent, an electrolyte salt, a polymerizable monomer, a crosslinking agent, and an initiator.
[0066] In some embodiments, the standing time is 24 to 72 hours.
[0067] In some embodiments, the curing temperature is 40-100°C, for example, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, or 100°C.
[0068] In some embodiments, the curing time is 1 to 10 h, for example, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, or 10 h.
[0069] According to a third aspect of the present application, a secondary battery is provided. The secondary battery includes the aforementioned composite electrolyte.
[0070] In some embodiments, the secondary battery is any one of a lithium ion secondary battery, a sodium ion secondary battery, a potassium ion secondary battery, a magnesium ion secondary battery, a calcium ion secondary battery, and an aluminum ion secondary battery.
[0071] In some embodiments, the secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. The positive electrode sheet, the negative electrode sheet and the separator are wound to obtain a battery core, and the raw materials of the composite electrolyte are injected and allowed to stand and solidify to make a secondary battery.
[0072] In some embodiments, the positive (negative) electrode sheet includes a positive (negative) electrode current collector and a positive (negative) electrode active material layer.
[0073] In some embodiments, the positive electrode current collector and the negative electrode current collector are independently selected from at least one of metal materials including metal foil (such as aluminum foil, silver foil, tin foil, iron foil, titanium foil, nickel foil, copper foil or alloy foil of the above metals), metal mesh (such as aluminum mesh, silver mesh, tin mesh, iron mesh, titanium mesh, nickel mesh, copper mesh or alloy mesh of the above metals).
[0074] In some embodiments, the positive (negative) electrode active material layer includes a positive (negative) electrode active material. Taking a lithium-ion secondary battery as an example, the positive electrode active material is at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel manganese aluminum oxide, etc., and the negative electrode active material includes at least one of carbon material, silicon material, carbon silicon material, etc.
[0075] In some embodiments, the raw materials of the positive (negative) electrode active material layer also include at least one of a conductive agent and a binder. Conductive agents include but are not limited to conductive graphite (such as KS-6, KS-15, SFG-6, SFG-15, SO, etc.), conductive carbon black (such as Super P, Super S, 350G, acetylene black, Ketjen black, etc.), conductive carbon fiber (such as VGCF, CNT) and graphene, etc. Binders include but are not limited to at least one of polyvinylidene fluoride, polytetrafluoroethylene, carboxymethyl cellulose, styrene-butadiene rubber, polyurethane, polyvinyl alcohol, polyvinyl butyral, etc.
[0076] In a fourth aspect of the present application, an electrical device is provided, the electrical device comprising the aforementioned secondary battery.
[0077] Among them, electrical equipment refers to any equipment that can use electrical energy and convert it into mechanical energy, thermal energy, light energy or other one or more forms of energy, such as electric motors, electric heat engines, electric light sources, etc. Among them, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Mobile devices can be mobile phones, laptops, drones, sweeping robots, electronic cigarettes, etc.; electric vehicles can be pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.
[0078] Compared with the prior art, the embodiments of the present application have the following advantages: Conventional inorganic fillers such as LLZO are large in size and difficult to be stably dispersed in the electrolyte. In the embodiment of the present application, an ultra-small MOF material with an average particle size not exceeding 10 nm is introduced, and it has a certain chemical stability, can form a uniform dispersion in the in-situ gel electrolyte, and is evenly distributed throughout the battery cell after injection, acting as a nucleation center during curing, and improving the ionic conductivity of the gel electrolyte after curing. The rate performance of the in-situ gel electrolyte is a key factor restricting its application. After adding ultra-small MOF, the rate performance of the battery cell can be greatly improved, and with the inherent safety properties of the in-situ gel electrolyte, its application can be greatly improved.
[0079] The composite electrolyte provided in the embodiments of the present application has basically no restrictions on the electrolyte system and the gel system, and is applicable to in-situ gel electrolytes for free radical polymerization and cationic polymerization.
[0080] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. DETAILED DESCRIPTION
[0081] The following will clearly and completely describe the concept of the present application and the technical effects produced in combination with the embodiments, so as to fully understand the purpose, features and effects of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of them. Based on the embodiments of the present application, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present application.
[0082] The embodiments of the present application are described in detail below. The described embodiments are exemplary and are only used to explain the present application, and should not be understood as limiting the present application.
[0083] In the description of this application, "several" means more than one, "many" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, "above", "below", "within", etc. are understood to include the number itself, and "about" means within the range of ±20%, 10%, 8%, 5%, 4%, 3%, 2%, 1%, 0.5%, 0.2%, 0.1%, etc. of the number itself. If there is a description of "first" or "second", it is only used to distinguish the technical features, and cannot be understood as indicating or implying the relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0084] In the description of the present application, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0085] The present application is described below in conjunction with specific embodiments.
[0086] The following examples involve a MOF material with an average particle size of less than 10 nm. Taking UiO-66 as an example, the preparation method is as follows: (1) Take 2 g of ZrCl4 and add it to a mixture of 3 mL of glacial acetic acid and 5 mL of isopropanol. Heat and stir at 500 rpm and 120 °C for 60 min. Centrifuge at 10,000 rpm to obtain a white precipitate, wash it with acetone, and vacuum dry it to obtain a zirconium oxide cluster powder.
[0087] (2) Take 75 mg of zirconium oxide cluster powder and add it to 0.5 mL of glacial acetic acid. Stir at 600 rpm to dissolve. Then add 1.25 mL of water and stir until clear. Then add 80 mL of ethanol and 50 mg of terephthalic acid (BDC) and react at room temperature for 2 hours. After the reaction is completed, evaporate at room temperature until a small amount of liquid remains. Collect the liquid and centrifuge at 14500 rpm for 2 hours, then centrifuge and wash with acetone and ethanol for 1.5 hours respectively. Vacuum dry the precipitate for 3 hours to obtain UiO-66.
[0088] refer to Nat Commun 15, 3434 (2024). The average particle size of UiO-66 obtained by this method is 5 nm. The preparation of other ultra-small MOF materials can refer to the above method and take the corresponding synthetic raw materials for preparation, which will not be repeated here.
[0089] Example 1 The present embodiment provides an electrolyte, which uses ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 1:1 as a solvent, and is added with LiPF6 (electrolyte lithium salt) with a final concentration of 1 mol / L, 2 wt% of butyl acrylate (polymerization monomer), 2 wt% of pentaerythritol tetraacrylate (cross-linking agent), 0.2 wt% of AIBN (azobisisobutyronitrile, initiator), and 5 wt% of UIO-66 with an average particle size of 5 nm.
[0090] This embodiment also provides a lithium-ion battery, wherein the above electrolyte is injected into a 5Ah soft-pack battery cell of a Gr-LCO (graphite-lithium cobalt oxide) system, the electrolyte is allowed to stand for 48 hours after injection, and cured at a high temperature of 70° C. for 3 hours to normalize the component capacity.
[0091] Example 2 This embodiment provides an electrolyte and a lithium ion battery made using the electrolyte. The difference from Embodiment 1 is that 5 wt % of UIO-66 with an average particle size of 5 nm is replaced by 5 wt % of ZIF-8 with an average particle size of 5 nm.
[0092] Example 3 This embodiment provides an electrolyte and a lithium ion battery made using the electrolyte. The difference from Embodiment 1 is that 5 wt % of UIO-66 with an average particle size of 5 nm is replaced by 5 wt % of MOF-801 with an average particle size of 5 nm.
[0093] Example 4 This embodiment provides an electrolyte and a lithium ion battery made using the electrolyte. The difference from Embodiment 1 is that the amount of UIO-66 is 0.1 wt %.
[0094] Example 5 This embodiment provides an electrolyte and a lithium ion battery made using the electrolyte. The difference from Embodiment 1 is that the amount of UIO-66 is 20 wt%.
[0095] Example 6 This embodiment provides an electrolyte and a lithium ion battery made using the electrolyte. The difference from Embodiment 1 is that the amount of UIO-66 is 50 wt%.
[0096] Example 7 This embodiment provides an electrolyte and a lithium ion battery made using the electrolyte. The difference from Embodiment 1 is that the amount of UIO-66 is 0.01 wt%.
[0097] Example 8 This embodiment provides an electrolyte and a lithium ion battery made using the electrolyte. The difference from Example 1 is that terephthalic acid in the preparation process of UiO-66 is replaced by 2-aminoterephthalic acid to prepare UiO-66-NH2 with an average particle size of about 5 nm.
[0098] Example 9 This embodiment provides an electrolyte and a lithium-ion battery made using the electrolyte. The difference from Embodiment 1 is that the average particle size of UiO-66 is about 9 nm (for example, the amount of ethanol can be adjusted to 40 mL).
[0099] Example 10 This embodiment provides an electrolyte and a lithium ion battery made using the electrolyte. The difference from Embodiment 1 is that the average particle size of UiO-66 is about 3 nm (for example, the amount of ethanol can be adjusted to 120 mL).
[0100] Embodiment 11 This comparative example provides an electrolyte and a lithium ion battery made using the electrolyte, which is different from Example 1 in that the amount of UIO-66 is 60 wt%.
[0101] Comparative Example 1 This comparative example provides an electrolyte and a lithium-ion battery made using the electrolyte, which differs from Example 1 in that it does not contain UIO-66 or other MOF materials.
[0102] Comparative Example 2 This comparative example provides an electrolyte and a lithium ion battery made using the electrolyte, which is different from Example 1 in that the amount of UIO-66 is 90 wt%.
[0103] Comparative Example 3 This comparative example provides an electrolyte and a lithium ion battery made using the electrolyte. The difference from Example 1 is that the average particle size of UIO-66 is 50 nm.
[0104] Comparative Example 4 This comparative example provides an electrolyte and a lithium ion battery made using the electrolyte. The difference from Example 1 is that the average particle size of UIO-66 is 100 nm.
[0105] Comparative Example 5 This comparative example provides an electrolyte and a lithium ion battery made using the electrolyte. The difference from Example 1 is that the average particle size of UIO-66 is 15 nm.
[0106] The lithium ion batteries prepared in the above embodiments and comparative examples were respectively taken to test their rate performance and low temperature performance. The specific methods are as follows: Rate performance: Charge to 4.53V at 0.2C constant current and constant voltage, discharge at 0.2C constant current, cut-off voltage 3.0V, record discharge capacity. Then charge to 4.53V at 0.2C constant current and constant voltage, discharge at 2C constant current, cut-off voltage 3.0V, record discharge capacity, calculate the ratio of 2C capacity to 0.2C capacity, which is the 2C discharge capacity ratio. Charge to 4.53V at 0.2C constant current and constant voltage, cut-off current 0.025C, leave for 5min, discharge at 0.5C constant current, cut-off voltage 3.0V, record charging capacity and constant current segment capacity. Then charge to 4.53V at 2C constant current and constant voltage, cut-off current 0.025C, leave for 5min, discharge at 0.5C constant current, cut-off voltage 3.0V, record charging capacity and constant current segment capacity, the ratio of constant current segment capacity to charging capacity is the 2C constant current charging ratio. Referring to the above process, the discharge capacity at different rates is measured through multiple cycles, and then the charge capacity at different rates is measured through multiple cycles.
[0107] Low temperature performance: At 25±3℃, fully charge at 0.2C, then discharge at 0.2C to 3.0V, and record the discharge capacity. Then fully charge at 0.2C, place the cell in -20℃, let it stand for 2h, and discharge at 0.5C to the cutoff voltage at -20℃. The cutoff voltage is 3V, and the discharge capacity is obtained. Calculate the ratio of the -20℃ discharge capacity to the 25℃ discharge capacity.
[0108] The results are shown in the following table: Table 1. Rate performance test results
[0109] It can be seen from the results in the table that compared with Comparative Example 1 which does not contain any MOF material, the rate performance of the embodiment has been significantly improved after the introduction of MOF materials with a certain content and particle size. In Comparative Example 2, due to the introduction of excessive MOF materials, the texture of the electrolyte has changed significantly, and the wetting ability has decreased significantly, so its 2C constant current charging and discharging capacity is less than half of that under 0.2C conditions. The particle size of the MOF material in Comparative Examples 3 to 5 increased, and sedimentation occurred during the standing process, and it was impossible to maintain a uniform dispersion state. The gel strength formed after in-situ curing was uneven, and it had a great impact on the distribution of the electrolyte after injection, resulting in some areas not being completely infiltrated, the electrolyte ion conductivity decreased significantly, and the rate performance was even worse than the case without any MOF material.
[0110] Table 2. Low temperature performance test results
[0111] From the results in Table 2, it can be seen that compared with Example 1, Example 8 uses an ultra-small MOF material with amino-modified ligands. The improvement in conductivity and the enhancement of the conductive network structure make it have less capacity attenuation under low temperature conditions and better low-temperature performance. In addition, compared with the MOF material used in Comparative Example 5, Comparative Example 6 introduces amino modification, and its low-temperature performance is improved to a certain extent; compared with Comparative Example 5, Example 1 changes the particle size of the MOF material, and its low-temperature performance is also enhanced to a certain extent; but when Example 8 adjusts the particle size and amino modification of the MOF material at the same time compared with Comparative Example 5, its improvement in low-temperature performance is significantly greater than that of Comparative Example 6, Example 1, and a simple combination of the two.
[0112] In addition, for Example 9 and Example 10, the detection was carried out according to the aforementioned method, and they had similar rate performance and low temperature performance as the other examples.
[0113] The present application is described in detail above in conjunction with the embodiments, but the present application is not limited to the above embodiments, and various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present application. In addition, the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
Claims
1. A composite electrolyte, characterized in that The composite electrolyte comprises a polymer electrolyte, the polymer electrolyte is doped with a MOF material, and the average particle size of the MOF material is no greater than 10 nm.
2. The composite electrolyte according to claim 1, characterized in that The mass percentage of the MOF material in the polymer electrolyte is 0.01-60 wt %.
3. The composite electrolyte according to claim 1, characterized in that The MOF material includes at least one of UiO-based, MOF-based, IRMOF-based, ZIF-based, BTC-based, MIL-based, and HKUST-based MOF materials.
4. The composite electrolyte according to claim 1, characterized in that The raw material for forming the polymer electrolyte includes polymer monomers, and the polymer monomers include at least one of acrylate monomers, ether monomers, carbonate monomers, oxalate monomers, and amide monomers.
5. The composite electrolyte according to claim 1, characterized in that The ligands of the MOF material are modified with amino groups.
6. The composite electrolyte according to claim 1, characterized in that The raw materials for forming the polymer electrolyte further include an initiator, and the initiator includes at least one of an azo initiator and a peroxide initiator.
7. The composite electrolyte according to claim 1, characterized in that The raw materials for forming the polymer electrolyte further include a crosslinking agent, and the crosslinking agent includes at least one of acrylates, ethers, carbonates, oxalates, and amides having two or more crosslinking sites.
8. The method for preparing the composite electrolyte according to any one of claims 1 to 7, characterized in that: The following steps are involved: The raw materials of the polymer electrolyte and the MOF material are mixed, and solidified after standing to obtain the composite electrolyte.
9. A secondary battery, characterized in that: The composite electrolyte comprises the composite electrolyte according to any one of claims 1 to 7.
10. Electrical equipment, characterized in that: A secondary battery comprising the secondary battery according to claim 9.
Citation Information
Patent Citations
Gel polymer electrolyte and preparation method thereof
CN102311605A
Composite solid electrolyte material and preparation method and application thereof
CN110085909A
Composite electrolyte membrane, fabrication methods and applications of same
CN111052477A
Composite solid-state electrolyte, solid-state battery and preparation method of solid-state battery
CN112563563A
Amino-containing MOF-based composite gel solid electrolyte with high specific surface area, preparation method and application thereof
CN112670565A
